(untitled) (Journal of Global Accounting, 2023)
This study was informed by perceived public outcry on the litany of tax burden which most often multiply collected from small businesses by government through different ministries and local government, thus indirectly stifling small businesses and limiting their growth and development. The study utilized the descriptive survey research design. The population comprised of 6698 registered micro and small enterprises in South-Eastern, Nigeria. The sample comprised of 384 respondents across the 5 South[1]Eastern States. The study relied on primary data; obtained from a structured questionnaire. The data was analysed using descriptive statistics; while, the t-test statistic is used to validate the hypotheses. The results revealed that there is a significant difference in the multiple taxes levied by tax agencies; and, such multiple taxations have a significant effect on micro and small businesses in South-Eastern, Nigeria. Based on these, the study recommended among others that government should consider increasing tax incentives and exemptions as this can attract investors who are potential tax payers; encourage voluntary compliance and ultimately lead to expansion of existing businesses in South-Eastern, Nigeria.